Structure of Hydrophobic Ambient-Pressure-Dried Aerogels Prepared by Sonohydrolysis of Tetraethoxysilane with Additions of N,N-Dimethylformamide - Chiappim, William [UNESP]; Awano, Carlos M. [UNESP]; Donatti, Dario A. [UNESP]; Vicente, Fabio S. de [UNESP]; Vollet, Dimas R. [UNESP] (Amer Chemical Soc, 2014)
Silica wet gels with the same silica content were prepared by the sonohydrolysis of tetraethoxysilane (TEOS) with additions of dimethylformamide (DMF). DMF plays a role in the overall hydrolysis/gelification/aging step of the sol gel process, providing more consolidated wet gels with larger syneresis degrees and densities. The structure of the as-obtained wet gels can be interpreted as being built up of mass-fractal domains with fractal dimension D = 2.2 and radius of gyration decreasing from about 14 to 12 nm with increasing quantity of DMF. Monolithic hydrophobic aerogels were prepared after washing of the wet gels with isopropyl alcohol (IPA), silylation with trimethylchrorosilane (TMCS), and ambient-pressure drying (APD). The specific surface area of the APD aerogels was found to be about 900 m(2)/g, and the mean silica particle size was about 2.0 nm, approximately independent of the DMF quantity, whereas the porosity decreased slightly with increasing amount of DMF, fairly accompanying the behavior of the radius of gyration of the precursor wet gels. The mass-fractal characteristics were preserved in the APD aerogels, but the radius of gyration of the mass-fractal domains was reduced to values between 2.8 to 4.0 nm, with the values decreasing slightly with the DMF quantity, and the fractal domains developed a surface-mass-fractal structure with the overall washing/silylation/APD treatment. The structural characteristics of the APD aerogels as determined by SAXS were found to be in notable agreement with those inferred from nitrogen adsorption.